Near threshold fatigue crack propagation in railways' steels: Comparison of two testing techniques. (December 2015) - Peixoto, D.F.C.; de Castro, P.M.S.T.
Highlights: Mode I fatigue crack growth thresholds of railway steels were determined. Two methods for evaluation of fatigue crack growth threshold were used. The data presented and learned lessons in conducting these texts are discussed. Data generated is compared with data published. Abstract: Mode I fatigue crack growth thresholds of steels for rail and wheel used in railways were determined according to two different procedures. Although fatigue crack propagation data in the Paris regime is usually straightforward to obtain, the same does not apply to the threshold regime, where crack growth rates are very small up to inexistent, and therefore tests are very time consuming. Furthermore, the very small fatigue crack growth rates involved in testing for threshold determination require very thorough and careful experimental procedures if extraneous effects – as for example interaction effects such as crack retardation or acceleration – are to be avoided. Two methods for evaluation of fatigue crack growth threshold value of the range of stress intensity factor were used: load shedding and constant maximum stress intensity factor with increasing load ratio R ( R  = minimum load/maximum load), taking into account the ASTM standard E647 prescriptions. The obtained results and lessons learned in conducting these tests are discussed, and the data generated is compared with data published.